Texture evolution and magnetic properties of Fe-4.5 wt% Si electrical steel with ND type columnar grains fabricated by rolling method - Junzhe Hu; Ruiyang Liang; Hao Wu; Yuan Tian; Feng Guo; Jiawei Feng; Wentao Zhang; Chengqian Sun (Journal of Materials Research and Technology)
Fe-4.5 wt% Si electrical steel is an exceptional soft magnetic material whose outstanding magnetic characteristics are significantly influenced by its texture. This work utilized ND type columnar grains (columnar grains is parallel to the normal direction), as the initial material to fabricate non-oriented 4.5 wt%Si electrical steel exhibiting superior magnetic characteristics. The EBSD technique was utilized to investigate the structural and textural evolution during hot rolling, normalizing, warm rolling, and annealing. Concentrate on the deformation and recrystallization characteristics of cube-oriented grains. The empirical data clearly indicated that ND type columnar grains display considerable initial organization and texture dependence during deformation and recrystallization processes. The robust cube-oriented grains that develop post-annealing originate from the retention of the original strong cube texture and the directional nucleation within the {100}<021> shear band. With an increase in annealing temperature, cube-oriented grains demonstrate aberrant development due to the augmented mobility of high-energy grain boundaries. The experimental steel has optimum magnetic characteristics during annealing at 1000 °C, due to its homogeneous organization, increased grain size, and robust λ(<001>∥ND) texture. The findings of this experiment can furnish a data foundation and theoretical backing for the fabrication of high-performance 4.5 wt% Si non-oriented electrical steel.